Effects of annealing temperature on shape transformation and optical properties of germanium quantum dots - Samavati, Alireza (2015)
The influences of thermal annealing on the structural and optical features of radio frequency (rf) magnetron sputtered self-assembled Ge quantum dots (QDs) on Si (100) are investigated. Preferentially oriented structures of Ge along the (220) and (111) directions together with peak shift and reduced strain (4.9% to 2.7%) due to post-annealing at 650 °C are discerned from x-ray differaction (XRD) measurement. Atomic force microscopy (AFM) images for both pre-annealed and post-annealed (650 °C) samples reveal pyramidal-shaped QDs (density ~ 0.26× 1011 cm−2) and dome-shape morphologies with relatively high density ~ 0.92 × 1011 cm−2, respectively. This shape transformation is attributed to the mechanism of inter-diffusion of Si in Ge interfacial intermixing and strain non-uniformity. The annealing temperature assisted QDs structural evolution is explained using the theory of nucleation and growth kinetics where free energy minimization plays a pivotal role. The observed red-shift ~ 0.05 eV in addition to the narrowing of the photoluminescence peaks results from thermal annealing, and is related to the effect of quantum confinement. Furthermore, the appearance of a blue-violet emission peak is ascribed to the recombination of the localized electrons in the Ge-QDs/SiO2 or GeOx and holes in the ground state of Ge dots. Raman spectra of both samples exhibit an intense Ge–Ge optical phonon mode which shifts towards higher frequency compared with those of the bulk counterpart. An experimental Raman profile is fitted to the models of phonon confinement and size distribution combined with phonon confinement to estimate the mean dot sizes. A correlation between thermal annealing and modifications of the structural and optical behavior of Ge QDs is established. Tunable growth of Ge QDs with superior properties suitable for optoelectronic applications is demonstrated.